Investigation on the Effect of Antibiotic and Multivitamin in the Formation of Biofilm in Urinary Tract Infection (UTI) Causing Pathogens - P Sajna, K; Paulraj, P; Balasupramaniam, V; Sajeesh, P; Chandramohan, M; Ketharin, T (International Journal of Engineering and Technology, 2019)
Urinary catheters make humans vulnerable to Urinary Tract Infection (UTI) by damaging the natural barrier of the body. Bacteria which are commonly related to this infection are Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa.  In this study   Klebsiella pneumoniae and Pseudomonas aeruginosa were obtained from the hospital.  Levofloxacin is a newly developed fluoroquinolone antibiotic, which is commonly used in clinical practice. The antibacterial effect of levofloxacin was studied using disk diffusion method. In this method the diameter of zone of inhibition in the presence of multivitamin was smaller than without multivitamin. The statistical analysis showed a significant difference in antibiotic sensitivity with and without multivitamin (p
Keywords: Biofilm; Levofloxacin; MBC; MIC; UTI